2013
DOI: 10.1371/journal.pone.0054313
|View full text |Cite
|
Sign up to set email alerts
|

It’s All in the Eyes: Subcortical and Cortical Activation during Grotesqueness Perception in Autism

Abstract: Atypical face processing plays a key role in social interaction difficulties encountered by individuals with autism. In the current fMRI study, the Thatcher illusion was used to investigate several aspects of face processing in 20 young adults with high-functioning autism spectrum disorder (ASD) and 20 matched neurotypical controls. “Thatcherized” stimuli were modified at either the eyes or the mouth and participants discriminated between pairs of faces while cued to attend to either of these features in uprig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 97 publications
(119 reference statements)
4
60
0
1
Order By: Relevance
“…Kliemann et al (2012) found that the ASD group was marginally slower than NTs overall and also identified fewer expressions; however, both groups were fastest for happy expressions. Zürcher et al (2013) found that the NT group was more accurate overall, while both groups made more inverted face errors; the NT group made more inverted mouth errors and the ASD group made fewer upright eye errors. The ASD group was also faster for inverted faces.…”
Section: Face Perception and Eye Fixation In Asdmentioning
confidence: 87%
See 4 more Smart Citations
“…Kliemann et al (2012) found that the ASD group was marginally slower than NTs overall and also identified fewer expressions; however, both groups were fastest for happy expressions. Zürcher et al (2013) found that the NT group was more accurate overall, while both groups made more inverted face errors; the NT group made more inverted mouth errors and the ASD group made fewer upright eye errors. The ASD group was also faster for inverted faces.…”
Section: Face Perception and Eye Fixation In Asdmentioning
confidence: 87%
“…The fMRI data demonstrate that forcing eye-region fixation in individuals with ASD tends to increase FG (Dalton et al, 2005; Perlman et al, 2011; Zürcher et al, 2013) and amygdala (Dalton et al, 2005; Kleinmann et al, 2012; Tottenham et al, 2013) activity, suggesting that face feature fixation manipulation can modulate and even normalize face sensitive cortical activity (Table 5). Although forced eye-fixation increases FG and amygdala activation in ASD, it is unclear if this provides support for either the active-avoidance or eye-area indifference theory.…”
Section: Face Perception and Eye Fixation In Asdmentioning
confidence: 92%
See 3 more Smart Citations